Carbohydrate utilization in the juvenile hybrid grouper (epinephelus fuscoguttatus ♀× epinephelus lanceolatus ♂) - Ruziah Ismail (2018)
Carbohydrate is one of the cheapest non-protein dietary components in fish diet that helps to metabolize other components and also improves the physical properties of pelleted feed. TGGG (Epinephelus fuscoguttatus, ♀) X (Epinephelus lanceolatus, ♂) , is a carnivorous fish that naturally has high requirement for the expensive dietary protein in the diet. Finding cheaper alternative energy sources to reduce the amount of protein in the diet is an important investigation in the effort to develop cost-effective diets for the sustainability of grouper farming. Considerable research on carbohydrate utilization in cultured fish has been conducted with inconsistent findings and mostly species-specific. In addition, little is known about the utilization of carbohydrate in TGGG. The present study was carried out to investigate the effects of different carbohydrate sources on fish performance and also to study the protein sparing effects of sago as a source of carbohydrate. In trial 1, four isoproteic (50% crude protein) and isolipidic (10% crude lipid) diets were formulated containing four different carbohydrate sources (tapioca starch, corn starch, sago starch and dextrin) at the same inclusion level (20%) and fed to triplicate groups of TGGG (13.78 ± 0.08 g mean initial weight). The fish were cultured in a flow-through seawater system and hand-fed twice a day with experimental diets until satiation for 67 days. At the end of feeding trial, the body weight gained (BWG), specific growth rate (SGR), and feed conversion ratio (FCR) of starch origins including Diets sago (798.01 %, 3.28 %/day and 1.19, respectively), Corn (782.09 %, 3.25 %/day and 1.17, respectively), and Tapioca (780.90%, 3.24 %/day and 1.15, respectively) were not affected and performed equally well. However, significantly lower BWG and SGR were observed in TGGG fed Diet Dextrin (707.66%, 3.12 %/day) and the finding was correlated with feed intake (FI) as significant reduction of feed intake was observed in Diet Dextrin. The survival of TGGG was 100% in all treatments with no significant difference (P>0.05) was detected. In contrast to growth performances, the hepatosomatic index (HSI) and viscerasomatic index (VSI) were significantly higher in Diet Dextrin than starch-based Diets. The whole-body moisture, ash and lipid were affected by dietary treatments. However, protein was not dependent on dietary carbohydrate sources. The glucose and total protein (P< 0.05) were significantly affected by dietary carbohydrate sources and no significant differences in cholestrol and triglyceride contents among treatments. As a conclusion, all the tested starches can be successfully used as carbohydrate sources in the diet for TGGG. In Trial 2, five experimental diets were formulated to be isolipidic (10% CL) and sago starch was used as a sole carbohydrate source. Two levels of protein (40 and 45% crude protein) and two levels of carbohydrate (25 and 30% carbohydrate) (coded as 45P 25C, 45P 30C, 40P 25C and 40P 30C, respectively) and Diet with 50% protein and 20% starch (50P20C) was formulated as a control diet. These diets were hand-fed to triplicate groups of TGGG (12.12 ± 0.08 g mean initial weight) for 57 days. The BWG (576.62-618.91%), FCR (1.48-1.59), survival (93.33-98.33%), and body indices except viscerasomatic index were independent of different dietary treatments. Meanwhile, proximate compositions of whole-body fish, liver and muscle were influenced by the different protein and carbohydrate levels. Apparent Digestibility Coefficient including dry matter, protein and lipid were also significantly influenced by the tested diets. The findings suggest that Sago starch has indicated some protein sparing where increasing carbohydrate level up to 30% and reducing protein to 40% was tolerated by TGGG. The present study has provided valuable knowledge to the aquaculture feed industry on different source of carbohydrates that can be used in the diets without deteriorating the fish performance and its potential in reducing the use of expensive protein in the diets.